2008
DOI: 10.1007/s10071-008-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Gaze following and gaze priming in lemurs

Abstract: Although primates have often been found to co-orient visually with other individuals, members of these same species have usually failed to use co-orientation to find hidden food in object-choice experiments. This presents an evolutionary puzzle: what is the function of co-orientation if it is not used for a function as basic as locating resources? Co-orientation responses have not been systematically investigated in object-choice experiments, and requiring co-orientation with humans (as is typical in object-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…Overall lemurs were successful with cues regarding the positional orientation of their competitor (front/back of body, or head turned in profile), but were not above chance when the only information regarding which competitor could see them was whether a headband covered the eyes or mouth. These findings build on previous studies of social cognition in lemurs, and suggest that these primates are sensitive to a number of behavioral indications of others' perception [37,[54][55][56][57]. Further, our data suggest that skills in this domain are related to a species' typical group size, implicating a possible evolutionary relationship between sociality and cognitive skills for outcompeting others for access to contestable resources.…”
Section: Discussionsupporting
confidence: 87%
“…Overall lemurs were successful with cues regarding the positional orientation of their competitor (front/back of body, or head turned in profile), but were not above chance when the only information regarding which competitor could see them was whether a headband covered the eyes or mouth. These findings build on previous studies of social cognition in lemurs, and suggest that these primates are sensitive to a number of behavioral indications of others' perception [37,[54][55][56][57]. Further, our data suggest that skills in this domain are related to a species' typical group size, implicating a possible evolutionary relationship between sociality and cognitive skills for outcompeting others for access to contestable resources.…”
Section: Discussionsupporting
confidence: 87%
“…For example Ruiz et al (2009) showed that lemurs co-orient with conspecific photographs to find hidden food but failed with humans (Anderson & Mitchell 1999). In addition, speciessuperiority in face perception is already known as an expertise effect for both humans and non-human primates (Tomonaga et al 1993;Parr et al 1998;Dahl et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies with lemurs suggest that attention is a major factor in the success of nonhuman primates to pass the object choice task (RUIZ et al 2009). It may be that extensive communicative and cognitive testing serves to focus the apes' attention on these declarative cues within a testing paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies utilizing this task have shown evidence of declarative comprehension in non-great apes including lemurs, dolphins, seals, goats, corvids, and canines (e.g. PACK and HERMAN 2007;RUIZ et al 2009;and see MIKLOSI and SOPRONI 2006 for a recent review). However, results from studies of great apes have been much less clear.…”
mentioning
confidence: 99%